Deterministic, stochastic, hybrid and band-limited modifications of Hotine’s integral - Featherstone, Will (Springer - Verlag, 2013)
Global Navigation Satellite System positioning of gravity surveys permits geoid computation via Hotine’s integral. A suite of modifications is presented so that the user can tune the relative contributions of truncation and data errors in a combined solution for a regional geoid model from gravity disturbances.